PSYCHOLOGICAL EFFECTS OF MANIPULATIVE EFFECTS IN SOCIAL RELATIONS - qosimova, sarvinoz (Центр Научных Публикаций (buxdu.uz), 2024)
in this article, the development of reflexive features in our country, which are manifested in an integrative way as a result of manipulative influences in students, the problem of its essence and main signs, the socio-psychological features of protecting students from manipulative influences, the ethnopsychological features of giving to manipulative influences in students and preventing various influences, the development of, talks about the priority character of communication motivation.